Supplementation of Omega-3 Polyunsaturated Fatty Acids Prevents Increase in Arterial Stiffness After Experimental Menopause. (January 2014) - Losurdo, Pasquale; Grillo, Andrea; Panizon, Emiliano; Cappellari, Gianluca Gortan; Fabris, Bruno; Bardelli, Moreno; Biolo, Gianni; Zanetti, Michela; Carretta, Renzo
Background: Menopause is associated with increased arterial stiffness, an independent marker of cardiovascular risk. Omega-3 polyunsaturated fatty acids (N3-PUFAs) are thought to have multiple cardiovascular benefits, including prevention of arterial stiffness. We investigated whether treatment with N3-PUFA prevents increase in arterial stiffness in ovariectomized rats, an animal model of experimental menopause. Methods: A total of 43 Wistar rats, 2 months old, were divided into 3 groups, control, sham surgery, normal diet (CTRL, n = 15); ovariectomy, normal diet (OVX, n = 14); and ovariectomy with N3-PUFA supplementation (0.8 g/kg/d in daily gavages administration; OVX + O3, n = 14). Two months after surgery, carotid–femoral pulse wave velocity (PWV) and arterial blood pressure (BP) were measured by carotid and femoral cannulation. Aortic morphometric measurements were performed after dissection. Results: Ovariectomy caused a significant increase in BP ( P < .05), PWV ( P < .0001), and elastic modulus ( P = .001) compared to CTRL. After ovariectomy, N3-PUFA supplementation completely prevented increase in arterial stiffness ( P < .0001 vs OVX) and BP ( P < .05 vs OVX) and resulted in a significant increase in body weight and aortic thickness. Conclusions: In an experimental model of menopause, N3-PUFA supplementation prevents arterial stiffening and other vascular changes induced by ovariectomy. These results represent a therapeutic benefit of N3-PUFAs in prevention of postmenopausal cardiovascular disease.